2022
DOI: 10.3390/pathogens11060611
|View full text |Cite
|
Sign up to set email alerts
|

HIV Latency in Myeloid Cells: Challenges for a Cure

Abstract: The use of antiretroviral therapy (ART) for Human Immunodeficiency Virus (HIV) treatment has been highly successful in controlling plasma viremia to undetectable levels. However, a complete cure for HIV is hindered by the presence of replication-competent HIV, integrated in the host genome, that can persist long term in a resting state called viral latency. Resting memory CD4+ T cells are considered the biggest reservoir of persistent HIV infection and are often studied exclusively as the main target for an HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 244 publications
0
9
0
Order By: Relevance
“…However, additional investigations seeking to elucidate the specific role of macrophages in HIV-1 transmission, particularly in mucosal tissues, are needed to shed light on the early events that contribute to the establishment of an infection. Finally, infected macrophages are not susceptible to the virus-induced cytopathic effect, and can thus participate, together with latently infected CD4+ T cells, in the early establishment and persistence of virus reservoirs in numerous host tissues (for recent reviews, see [ 2 , 10 ]). As recently shown [ 3 ], these virus reservoirs in myeloid cells can be detected over several years in patients on cART.…”
Section: Macrophages As Cellular Targets Of Hiv-1 In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…However, additional investigations seeking to elucidate the specific role of macrophages in HIV-1 transmission, particularly in mucosal tissues, are needed to shed light on the early events that contribute to the establishment of an infection. Finally, infected macrophages are not susceptible to the virus-induced cytopathic effect, and can thus participate, together with latently infected CD4+ T cells, in the early establishment and persistence of virus reservoirs in numerous host tissues (for recent reviews, see [ 2 , 10 ]). As recently shown [ 3 ], these virus reservoirs in myeloid cells can be detected over several years in patients on cART.…”
Section: Macrophages As Cellular Targets Of Hiv-1 In Vivomentioning
confidence: 99%
“…Intriguingly, it was suggested that gut macrophages are resistant to HIV-1 infection (for reviews, see [ 2 , 49 ]), even though it was reported that duodenal macrophages from gut biopsies of ART-suppressed people living with HIV can express viral antigens [ 50 ]. In vitro, it has been shown that intestinal macrophages are less permissive than cervicovaginal macrophages to HIV-1 infection and replication [ 51 ].…”
Section: Macrophages As Cellular Targets Of Hiv-1 In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, while CD4+ T cells represent the main reservoir of latently infected cells, monocytes and macrophages are becoming increasingly recognized as additional sources of latent viral reservoirs. 5 This review focuses primarily on the roles of RNA molecules in HIV regulation of HIV latency in CD4+ T cells and lymphocytic cell lines; however, observations of their roles in monocytes, macrophages, and promonocytic cell lines are also discussed.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-infected monocytes could provide an important mechanism to disseminate the virus to sites, like the central nervous system (CNS) and male genital system, where evidences for compartmentalization of viral populations had been identified. [ 5 ] One possibility is that monocytes are being infected by macrophage-tropic viruses replicating in tissue macrophage. [ 6 ] Defining genetic determinants of viruses in monocytes could enhance our overall understanding of macrophage-tropic viruses in different anatomic sites and have implications for the design of curative strategies for HIV.…”
mentioning
confidence: 99%